Penerapan Metode Pakistani untuk Meningkatkan Kualitas Pembelajaran Tahfiz Al-Qur’an di Mahir Tahfiz School - Nurhayati, Nurhayati; Tamyis (UNISAN JURNAL, 2025)
This study aims to analyze the implementation of the Pakistani Method in improving the quality of Qur’an memorization learning at Mahir Tahfiz School Jakarta. The Pakistani Method is a tahfiz approach emphasizing intensive repetition (takrar), accurate articulation (makhraj), and gradual mastery through structured daily recitation and muraja’ah sessions. This research employed a qualitative approach using observation, in-depth interviews, and documentation to obtain a comprehensive understanding of the method’s application. The findings reveal that the use of the Pakistani Method significantly enhances memorization accuracy, the speed of mastering new verses, and students’ consistency in revision. Furthermore, the method increases learners’ motivation through measurable daily targets and intensive guidance from tahfiz instructors. Challenges such as diverse student abilities and limited instructional time were identified but addressed through schedule adjustments and differentiated guidance. Overall, the study concludes that the Pakistani Method is effective in improving the quality of Qur’an memorization learning within modern tahfiz school environments.